Audiological Rehabilitation in Severe to Profound Hearing Impairment - Satu Turunen-Taheri; Per-Inge Carlsson; Sten Hellstrom (Achievements and Challenges of Medicine and Medical Science Vol. 5, 2024)
Background: Hearing impairment affects communication and reduces participation and inclusion in society on several levels. Hearing impairment can be mild (26–40 dB HL), moderate (41–70 dB HL), severe (71–90 dB HL), or profound (more than 91 dB HL). Audiological rehabilitation involves various professionals such as audiologists, hearing rehabilitation educators, welfare officers, psychologists, physicians, and technicians. To say that a patient has participated in group rehabilitation, the patient must have been taught in a group by several hearing care professionals. Purpose: The purpose of this study was to identify and report demographic data of patients with severe to profound hearing loss, assess participation in audiological rehabilitation and analyze the benefits of various rehabilitation methods. Materials and Methods: Data on 4286 patients with severe to profound hearing impairments registered in the Swedish Quality Register of Otorhinolaryngology over a period from 2006–2015 were studied. Demographic data, gender differences, audiological rehabilitation and benefits of the rehabilitation were analyzed. Statistical calculations were performed with the IBMVR SPSSVR Statistics version 24. The data from the general questionnaire and the QoL parameters were analyzed using unpaired t-tests, and the categorical data were analyzed using chi-square tests. Results: The study comprises 50.3% (n=2157) males and 49.7% (n=2129) females, with a mean age of 69 years (SD 17.3). Group rehabilitation and visits to a hearing rehabilitation educator provided the most benefits in audiological rehabilitation. Only 40.5% of the patients received extended audiological rehabilitation, of which 54.5% were women. A total of 9.5% of patients participated in group rehabilitation, with 59.5% being women. Women also visited technicians, welfare officers, hearing rehabilitation educators, psychologists, physicians and ENT specialists and received communication rehabilitation in a group and fit with cochlear implants significantly more often than did men. Conclusions: The study emphasizes the importance of being given the opportunity to participate in group rehabilitation and meet a hearing rehabilitation educator to experience the benefits of hearing rehabilitation. In the present study, significantly more women than men received audiological rehabilitation with various hearing care professionals. There is a need to offer extended audiological rehabilitation, especially in terms of gender differences, to provide the same impact for women and men. Implications for Rehabilitation: Significantly more women than men with severe to profound hearing impairment receive audiological rehabilitation. Hearing impairment appears to have a significantly more negative impact on women’s quality of life than men’s. It is important to offer extended audiological rehabilitation to all patients with severe to profound hearing loss to obtain equal hearing health care regardless of gender.